Increased Kappa/Lambda Hybrid Antibody in Serum Is a Novel Biomarker Related to Disease Activity and Inflammation in Rheumatoid Arthritis - Lang Yi; Mingju Hao; Tian Lu; Guigao Lin; Lida Chen; Ming Gao; Gaowei Fan; Dong Zhang; Guojing Wang; Xin Yang; Yulong Li; Kuo Zhang; et al. (Mediators of Inflammation)
The κ/λ hybrid antibodies in normal human serum were reported recently, but their clinical relevance has not yet been explored. Rheumatoid arthritis (RA) is one of the major joint diseases, and the early diagnosis and treatment of RA remain a challenge. Here, we developed a double-sandwich enzyme-linked immunosorbent assay system to quantify relative serum κ/λ hybrid antibody levels in RA patients, osteoarthritis (OA) patients, and healthy controls (HC) in order to assess their potential use as a serological biomarker of early disease and clinical activity and to preliminarily investigate their immunomodulatory roles in RA. Surprisingly, we found that κ/λ hybrid antibody was markedly increased in both early and established RA. Serum κ/λ hybrid antibody levels were significantly correlated with clinical indexes and inflammatory markers in RA. Further analysis showed a positive correlation between κ/λ hybrid antibody levels and the 28-joint disease activity score (DAS28). In conclusion, serum κ/λ hybrid antibodies in RA were identified for the first time. High levels of κ/λ hybrid antibody may be a useful tool in distinguishing early RA from OA and HC. We suggest κ/λ hybrid antibody as a marker for disease activity. The increased κ/λ hybrid antibodies were associated with inflammatory conditions in RA.